TRADE INTENSITY AND REVEALED COMPARATIVE ADVANTAGE IN AGRICULTURAL COMMODITIES: AN ANALYSIS FOR PAKISTAN AND CHINA - Muhammad Bilal Ahsan; Nasir Nadeem; muhammad adnan nadeem (Journal of Animal and Plant Sciences, 2025)
China and Pakistan share a longstanding partnership that has deepened over the years, particularly through initiatives like the China-Pakistan Economic Corridor (CPEC). China is investing $46 billion in the CPEC program, including infrastructure, energy, and agriculture. Extant research was planned to identify the comparative advantage of both countries in the agriculture sector. Further, this study measures the overall trade intensity and trade trend during 2004 through 2023. . The analysis reveals that Pakistan has an enormous trade deficit. Overall bilateral trade shows an increasing trend both in export and import. Out of 37 agriculture commodities, Pakistan has a comparative advantage in 11 agriculture commodities, whereas China has a comparative advantage in 9. The study further discloses that Pakistan's export trade intensity has decreased, and import trade intensity has increased since 2013. However, the RCA index of different commodities indicates a statistically significant advantage of Chinese products over Pakistani products. Furthermore, the Pakistani government should formulate favourable policies for higher growth of sectors with high comparative advantage; ultimately, this can increase earnings from exports, create employment opportunities, and increase global competitiveness.
Keywords: China-Pakistan; Revealed Comparative Advantage; Trade intensity; Export; Import